Educação para desenvolvimento sustentável com foco na interação com a infraestrutura verde de Passo Fundo - Reolão, Michele Rocha (2019)
The urban world population exceeds the population living in rural areas, and cities need to adapt to this new population contingent that lives in urban areas. Thus, green infrastructure plays a key role in the issues surrounding sustainable development. Concern over the decline of human experience with nature is addressed by considering the potential of green infrastructure to promote experiences with nature and so assist in the promotion of education for sustainable development in view of the Sustainable Development Goals (ODS), especially ODS 11 - Sustainable Cities and Communities. This research observed how the interaction of the population with the green infrastructures is related to the issues attachment to nature and environmental behavior. In order to reach this objective, the applied methodology was divided in three stages: the first one to characterize the green infrastructures of the city of Passo Fundo | RS, city chosen as a case study; the second stage of characterization of people's interactions with the green infrastructures of Passo Fundo, through study of the attachment with the parks and the practice of attitudes for environmental reasons; and the third stage of analysis and stimulation of the contact of the urban population with the green infrastructures. In this way, three parks were identified as a case study, considering their relevance to the city and the region. In this context, questionnaires were applied that showed results of how the interaction of people with the green infrastructure of the cities present a strong relation with the attachment and bond that people create with these spaces and with the practice of activities for environmental reasons. In addition, actions were carried out with the intention of sensitizing the population, which evidenced people's interest in issues related to nature, and also the possibility of creating people's attachment with these spaces.